Penerapan Pembelajaran Berbasis Teks pada Siswa Kelas V Sekolah Dasar - Nala Rahmawati; Haris Supratno; Ratih Asmarani (Universitas Islam Madura, 2019)
The purpose of this research is to describe the learning process, teacher activities, student activities, and student learning outcomes before and after text based learning. This research is using applied type research methods with qualitative and quantitative approaches. This research uses data analysis techniques from the results of observations, interviews with a teachers and 2 students in fifth grade, and student learning outcomes. The results of study from application of text-based learning at fourth meeting showed that the learning process was effective. In the learning process, learning component used is the scientific approach, methods vary, media that focuses on the blackboard, and the learning environment is carried out in class V. The teacher's activities in learning is to guide students from the beginning to the end of the implementation of the learning process, starting from explaining the reading text, asking students to ask qeustions, giving assignments to students both individually and in groups, and giving a question to students. Thus student activities are carrying out learning activities in accordance with the intructions of the teacher, starting from reading the text by randomly appointed by the teacher, paying attention to the teacher’s explanation, asking questions, doing assignments, and answering questions from the teacher. Stuudent learning outcomes in before learning show the average value of students is 61,62 and after the text-based learning process shows that at first meeting the average value of students is 78,10, the average value of the second meeting is 80, the average value the third meeting is 80,40, and the average value of student learning outcomes at the fourth meeting is 86,08. Keywords: Learning, Text Based, Curriculum 2013. Abstrak: Tujuan dari penelitian ini adalah untuk mendeskripsikan proses pembelajaran, aktivitas guru, aktivitas siswa, dan hasil belajar siswa sebelum dan sesudah pembelajaran berbasis teks. Penelitian ini adalah menggunakan metode penelitian jenis terapan dengan menggunakan pendekatan kualitatif dan kuantitatif. Penelitian ini menggunakan teknik analisis data dari hasil observasi, wawancara pada guru dan dua siswa kelas V, serta hasil belajar siswa. Hasil penelitian dari penerapan pembelajaran berbasis teks pada empat pertemuan menunjukkan bahwa dalam proses pembelajaran berjalan dengan efektif. Pada proses pembelajaran, komponen pembelajaran yang digunakan adalah pendekatan saintifik, metode bervariasi, media yang berfokus pada papan tulis, dan lingkungan belajar dilaksanakan diruang kelas V. Aktivitas guru dalam pembelajaran adalah membimbing siswa dari awal hingga akhir pelaksanaan proses pembelajaran, mulai dari menjelaskan teks bacaan, meminta siswa untuk bertanya, memberikan tugas pada siswa baik secara individu maupun kelompok, dan memberikan sebuah pertanyaan pada siswa. Demikian aktivitas siswa adalah melaksanakan kegiatan pembelajaran sesuai dengan instruksi dari guru, mulai dari membaca teks dengan cara ditunjuk guru secara acak, memperhatikan penjelasan guru, bertanya, mengerjakan tugas, dan menjawab pertanyaan dari guru. Hasil belajar siswa pada sebelum pembelajaran menunjukkan nilai rata-rata siswa adalah 61,62 dan sesudah proses pembelajaran berbasis teks menunjukkan bahwa pada pertemuan pertama nilai rata-rata siswa adalah 78,10, nilai rata-rata pertemuan kedua adalah 80, nilai rata-rata pertemuan ketiga adalah 80,40, dan nilai rata-rata hasil belajar siswa pada pertemuan keempat adalah 86,08.